Seaweed Application in Making Meatballs Substitute for Borax at Meatball Traders of Overseas Solo Residents - Dasir, Dasir; Sunardi, Sunardi (Universitas Muhammadiyah Palembang, 2022)
The use of borax as an additive in food processing is still used by some meatball traders with the aim of improving the color, shape, taste, texture, and extending the shelf life, even though based on the 1998 Menkes regulation the use of borax in food processing has been prohibited because it can cause disease. Another alternative that can be used is a safe additive with the same function to improve the texture and elasticity of the meatballs, namely seaweed. The purpose of this service activity is to provide an understanding and practice of making meatballs using additional ingredients of seaweed as a substitute for borax to meatball traders in Talang Putri (Plaju) Palembang who are members of the Association of Meatball Traders of Solo Overseas Residents. The results of the activity showed that the counseling participants could make meatballs with the addition of seaweed additives without any significant obstacles, because there was no difference in principle with the making of meatballs that they had been doing so far. So that the results of the meatballs obtained are quite good in terms of existing quality standards based on color, aroma, taste and texture or elasticity.